2015
DOI: 10.1063/1.4917207
|View full text |Cite
|
Sign up to set email alerts
|

Tunable zinc interstitial related defects in ZnMgO and ZnCdO films

Abstract: High-temperature stability of postgrowth-annealed Al-doped MgxZn1-xO films without the phase separation effect J. Vac. Sci. Technol. B 30, 061201 (2012); 10.1116/1.4754813 Effect of substrate temperature on the properties of transparent conductive ZnO:Al thin films prepared by RF sputtering J. Vac. Sci. Technol. A 29, 051506 (2011); 10.1116/1.3610175 Phonon dynamics of Zn(Mg,Cd)O alloy nanostructures and their phase segregation Effect of high-energy electron beam irradiation on the properties of ZnO thin films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Analysis on ZnO powder reveals peak at 988 eV and a shoulder at 991 eV. The shoulder peak at 991 eV was suggested previously by Li et al as interstitial Zn present as defect sites in the ZnO lattice 33 . These changes between metallic and oxidised states are thus much clearer in the Auger spectra than in the core level spectra and reflect changes in the M (valence) levels of Zn.…”
Section: Xps and Xaessupporting
confidence: 61%
See 1 more Smart Citation
“…Analysis on ZnO powder reveals peak at 988 eV and a shoulder at 991 eV. The shoulder peak at 991 eV was suggested previously by Li et al as interstitial Zn present as defect sites in the ZnO lattice 33 . These changes between metallic and oxidised states are thus much clearer in the Auger spectra than in the core level spectra and reflect changes in the M (valence) levels of Zn.…”
Section: Xps and Xaessupporting
confidence: 61%
“…S5. For Zn metal it was reported that there are peak positions of 992 (major) and 996 (minor) 32 , while for the oxide they are 988 and 991 respectively 33 . Zn metal shows major peaks at kinetic energy of 996 eV and 992.5 eV and minor peaks at 989.3 eV and 986 eV ( fig.…”
Section: Xps and Xaesmentioning
confidence: 99%
“…were observed between synthesised catalysts (Figure S5a). The Zn(LM 2 ) Auger peak for zinc oxide is at 988 eV with a minor satellite contribution at 991 eV, [50] whilst for metallic zinc these peaks are much more shifted than the core levels, to 992 eV and 996 eV respectively [51] . Therefore, the Zn(LM 2 ) Auger electron spectra were also analysed, since it has higher discrimination for chemical changes (Figure S5b).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the coordinated Zn can be identified in the Zn LMM Auger spectrum measured by X-ray photoelectron spectroscopy (XPS). [32,33] The coordinated Zn peak centered at 496.7 eV, in addition to the lattice Zn peak centered at 499.8 eV, is evident in Figure 3d. [34] Likewise, a shoulder peak centered at 532.6 eV in the spectrum of the O1s core level of the piZn confirms the interaction between Zn ions and the carbonyl oxygen atoms ( Figure S10, Supporting Information).…”
mentioning
confidence: 96%